ARTMAN, Amy Collier. The Miracle Lady: Kathryn Kuhlman and the Transformation of Charismatic Christianity. (28th October 2021) - Ramsey, Ryan
Abstract : ARTMAN, Amy Collier. The Miracle Lady: Kathryn Kuhlman and the Transformation of Charismatic Christianity. Library of Religious Biography Series. Grand Rapids, MI: Eerdmans, 2019. 244pp. Pbk. ISBN: 978-0-8028-7670-6. $28.